Microchip electrophoresis utilizing an in situ photopolymerized Phos-tag binding polyacrylamide gel for specific entrapment and analysis of phosphorylated compounds. Issue 18 (21st August 2017) - Yamamoto, Sachio; Himeno, Miyuki; Kobayashi, Masaya; Akamatsu, Miki; Satoh, Ryosuke; Kinoshita, Mitsuhiro; Sugiura, Reiko; Suzuki, Shigeo
Abstract : A method was developed for the specific entrapment and separation of phosphorylated compounds using a Phos-tag polyacrylamide gel fabricated at the channel crossing point of a microfluidic electrophoresis chip. Abstract : A method was developed for the specific entrapment and separation of phosphorylated compounds using a Phos-tag polyacrylamide gel fabricated at the channel crossing point of a microfluidic electrophoresis chip. The channel intersection of the poly(methyl methacrylate)-made microchip was filled with a solution comprising acrylamide, N, N -methylene-bis-acrylamide, Phos-tag acrylamide, and 2, 2′-azobis[2-methyl- N -(2-hydroxyethyl)propionamide], which functioned as a photocatalytic initiator. In situ polymerization at the channel crossing point was performed by irradiation with a UV LED laser beam. The fabricated Phos-tag gel (100 × 100 × 30 μm) contains ca. 20 fmol of the Phos-tag group and therefore could entrap phosphorylated compounds at the femtomolar level. The electrophoretically trapped phosphorylated compounds were released from the gel by switching the voltage to deliver high concentrations of phosphate and EDTA in a background electrolyte. The broad sample band eluted from the gel was effectively reconcentrated at the boundary of a pH junction generated by sodium ions delivered from the outlet reservoir. The reconcentrated sample components were then separated and fluorometrically detected at the end of the separation channel. Under the optimized conditions, the phosphorylated compounds were concentrated by a factor of 100-fold, and the peak resolution was comparable to that obtained by pinched injection. This method was successfully utilized to preconcentrate and analyze phosphorylated peptides in a complex peptide mixture.